2020
DOI: 10.3390/ijerph17124457
|View full text |Cite
|
Sign up to set email alerts
|

Positive Youth Development and Adolescent Depression: A Longitudinal Study Based on Mainland Chinese High School Students

Abstract: There are several limitations of the scientific literature on the linkage between positive youth development (PYD) attributes and adolescent psychological morbidity. First, longitudinal studies in the field are limited. Second, few studies have used validated PYD measures to explore the related issues. Third, few studies have used large samples. Fourth, limited studies have been conducted in mainland China. In this study, we conducted a longitudinal study using two waves of data collected from 2648 junior high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 68 publications
7
59
0
Order By: Relevance
“… Benson et al (2006) argued that PYD could be shaped by both external and internal assets, which contributes to adolescent well-being and later success. Consistent with the PYD theories, research findings showed that PYD qualities were linked to a broad range of adolescent developmental outcomes including internalizing and externalizing behaviors, psychological adjustment as well as prosocial behavior ( Eichas et al, 2010 ; Schwartz et al, 2010 ; Ciocanel et al, 2017 ; Shek and Zhu, 2018 ; Zhou et al, 2020 ). However, few studies have addressed the mediating role of life satisfaction in the influence of PYD qualities on adolescent developmental outcomes, particularly in different Chinese societies ( Sun and Shek, 2010 , 2012 ).…”
Section: Introductionmentioning
confidence: 69%
“… Benson et al (2006) argued that PYD could be shaped by both external and internal assets, which contributes to adolescent well-being and later success. Consistent with the PYD theories, research findings showed that PYD qualities were linked to a broad range of adolescent developmental outcomes including internalizing and externalizing behaviors, psychological adjustment as well as prosocial behavior ( Eichas et al, 2010 ; Schwartz et al, 2010 ; Ciocanel et al, 2017 ; Shek and Zhu, 2018 ; Zhou et al, 2020 ). However, few studies have addressed the mediating role of life satisfaction in the influence of PYD qualities on adolescent developmental outcomes, particularly in different Chinese societies ( Sun and Shek, 2010 , 2012 ).…”
Section: Introductionmentioning
confidence: 69%
“…Finally, although the present findings give support to the concurrent validity of the measure using measures on whether the participants will join similar programs, whether the participants will recommend others to join, and overall satisfaction, it would be helpful to use other external criteria not related to overall satisfaction of the programs. In particular, researchers can use measures of positive youth development (PYD) such as psychosocial competence (Zhou et al 2020) and academic performance as external criteria for the concurrent validity of the measure. Despite these limitations, the present study contributes to the limited SL literature on the value of SL learning activities from the perspective of the service recipients.…”
Section: Discussionmentioning
confidence: 99%
“…We recruited four high schools in mainland China from the schools participating in the “Tin Ka Ping P.A.T.H.S. Project” [ 26 , 27 , 28 ] to join the study. For Grade 7 students, 1362 and 1305 students joined in Wave 1 and Wave 2, respectively (attrition rate = 4.19%).…”
Section: Methodsmentioning
confidence: 99%